Myanmar, the Rohingya crisis, and further EU sanctions - Heiduk, Felix (2018)
Zusammenfassung: The violence against the Rohingya, which has led hundreds of thousands of Rohingya to seek refuge in Bangladesh, has severely damaged Myanmar’s international image. In response to the deterioration of the human rights situation in Myanmar in October 2018, the European Union (EU) threatened to withdraw the trade preferences that ensure the country has duty-free access to the EU common market. It seems highly plausible, however, that such measures would fail to alter the political calculations of the Burmese government or of the military. Instead, a withdrawal of the trade preferences would primarily hit the mostly female workers in the country’s textile industry. The EU and its Member States should therefore consider a combination of specific sanctions against military enterprises as well as tightened entry bans and account freezes that are directed at leading military personnel. These targeted sanctions against Myanmar’s armed forces should be flanked by an increase in the level of diplomatic engagement with civilian actors in the country